2018
DOI: 10.1016/j.ejmech.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided design of potent and permeable inhibitors of MERS coronavirus 3CL protease that utilize a piperidine moiety as a novel design element

Abstract: There are currently no approved vaccines or small molecule therapeutics available for the prophylaxis or treatment of Middle East Respiratory Syndrome coronavirus (MERS-CoV) infections. MERS-CoV 3CL protease is essential for viral replication; consequently, it is an attractive target that provides a potentially effective means of developing small molecule therapeutics for combatting MERS-CoV. We describe herein the structure-guided design and evaluation of a novel class of inhibitors of MERS-CoV 3CL protease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 46 publications
6
100
0
Order By: Relevance
“…A dipeptidyl transition state 3CL pro inhibitor GC376 (71) (FRET) assay [115]. Another pyrrolidinone based peptide GC813 (72) as well as its derivatives 73-74 displayed inhibition for MERS-CoV with EC50 values of 0.5 mM, 0.5 mM, and 0.8 mM in cell culture [116]. Kenichi et al reported new non-peptide SARS-CoV 3CL pro inhibitors [117] by introducing decahydroisoquinoline at the S2 position by connecting the cyclohexyl group of the substrate-based inhibitor 75 (Fig.…”
Section: Mers-cov and Sars-cov Pl Proteases Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dipeptidyl transition state 3CL pro inhibitor GC376 (71) (FRET) assay [115]. Another pyrrolidinone based peptide GC813 (72) as well as its derivatives 73-74 displayed inhibition for MERS-CoV with EC50 values of 0.5 mM, 0.5 mM, and 0.8 mM in cell culture [116]. Kenichi et al reported new non-peptide SARS-CoV 3CL pro inhibitors [117] by introducing decahydroisoquinoline at the S2 position by connecting the cyclohexyl group of the substrate-based inhibitor 75 (Fig.…”
Section: Mers-cov and Sars-cov Pl Proteases Inhibitorsmentioning
confidence: 99%
“…Groutas et al reported the novel class of peptidomimetic MERS-CoV3CL pro inhibitors that embody a piperidine moiety [116]. These inhibitors were designed based on the dipeptidyl aldehyde bisulfite adduct inhibitor, designated GC376 (84, Fig.…”
Section: Mers-cov and Sars-cov Pl Proteases Inhibitorsmentioning
confidence: 99%
“…We aligned the crystal structures of M pro of SARS-CoV, MERS-CoV and SARS-CoV-2 to compare the structures and the residues of the catalytic site. The catalytic site for SARS-CoV and SARS-CoV-2 are the same: His41-Cys145 [52], whereas for MERS-Cov it is His41-Cys148 [52] (Fig. 2).…”
Section: Sars-cov-2 Drug Discovery Effortsmentioning
confidence: 98%
“…PLpro is controlled by a wide range of components, mutations, and other effects. Antiviral drugs, such as PLpro inhibitors and 3CLpro inhibitors (Table 2), have been studied for their innate immunosuppression profiles [41,42]. Nsp5 is widely involved in virus-encoded polyproteins (ppla, pplab) and 16 nsps processing; therefore, nsp5 is essential and indispensable for virus survival.…”
Section: Proteolysismentioning
confidence: 99%